Exploring Legal Frameworks for the Clinical Use of Psychedelic Substances in Mental Health Treatment - Sucinta, Ardianto; Kusumaningrum, Anggraeni Endah (UNTAG Law Review, 2024)
In recent years, interest in the use of psychedelic substances in the treatment of mental disorders has increased significantly. Recent research shows the potential of psychedelic substances such as psilocybin, LSD, and MDMA to treat disorders such as major depression, post-traumatic stress disorder (PTSD), and substance addiction. However, the clinical use of psychedelic substances remains very limited due to significant legal obstacles. This study aims to explore the relevant legal framework for the clinical use of psychedelic substances in the treatment of mental disorders. By considering various rules and regulations at national and international levels, we explore the challenges and opportunities in creating an enabling legal framework for the clinical use of psychedelic substances. Our analysis highlights differences in legal approaches between countries, with some countries such as the United States beginning to pave the way for research and clinical use of psychedelic substances in mental treatment, while other countries still maintain a strict approach to the use of psychedelic substances. The results of this study provide important insights for policymakers, health practitioners, and researchers to understand the existing legal framework and challenges faced in integrating psychedelic substances into clinical practice. Thus, this study may help guide the development of policies that promote safe and responsible access to psychedelic therapy in the treatment of mental disorders.